PERSEPSI MASYARAKAT TERHADAP KEBERADAAN PERKEBUNAN KELAPA SAWIT PT. PERKEBUNAN NUSANTARA VIII TAMBAKSARI AFDELING SINDANGSARI, SUBANG - Zahwa, Maulina; Ernah, Ernah (Universitas Galuh, 2023)
Indonesia is the country with the largest oil palm plantation in the world. One of the companies that manages oil palm plantations is PT Perkebunan Nusantara (PTPN) VIII Tambaksari afdeling sindangsari plantation, Subang. Before it became an oil palm plantation land, most people planted pineapple crops. After the existence of oil palm plantations, many communities were helped by the economy. However, some communities with farmers' livelihoods have complained that pineapple plantations continue to narrow because they are prepared for oil palm development. Based on these problems, this study aims to describe the characteristics of communities around oil palm plantations and find out the community's perception of the existence of oil palm plantations at PTPN VIII Kebun Tambaksari Afdeling Sindangsari, Subang in terms of social impacts and economic impacts using descriptive analysis and scoring analysis. The method used in this study is quantitative with a type of survey research. The results showed that the company had a positive impact on the communities around the PTPN VIII Kebun Tambaksari oil palm plantation on social impact indicators which included the quality of education, facilities and infrastructure, social values with an average score of 68.08 included in the positive category and economic impact indicators which included labor, new work ventures, and the number of residents and job opportunities with an average score of 71.47 included in the positive category.